Dampak Pemasaran Digital, Kualitas Layanan Dan Harga Terhadap Kepuasan Pelanggan Pada The Crown Clinic Aesthetic & Beauty Care Kediri Melalui Keputusan Pembelian Sebagai Variabel Intervening - Enike Kuswahyuliana; Eka Askafi; Abu Talkah (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This research was carried out by The Crown Clinic Aesthetic & Beauty Care Kediri and focuses on digital marketing, service quality, and price. The purpose of this research is to examine the effect of digital marketing, service quality, and pricing on customer satisfaction at The Crown Clinic Aesthetic & Beauty Care Kediri, with purchasing decisions as an intervening variable. This research is a quantitative research by involving exogenous or independent variables, notably digital Marketing, Pricing, and Service Quality. The subject of this research is a customer or member who receives treatment at The Crown Clinic Aesthetic & Beauty Care by having A total of 94 respondents will be selected using Accidental Sampling techniques. This research utilizes data collecting methods. Path analysis is the data analysis employed. The results of this study indicate that; (1) there is an effect of digital marketing on purchasing decisions, (2) service quality directly has an influence on purchasing decisions, (3) prices have a positive and significant influence on purchasing decisions, (4) digital marketing does not have a positive and significant influence on satisfaction customers, (5) service quality does not have a positive and significant effect on customer satisfaction, (6) price does not have a positive and significant effect on customer satisfaction, (7) digital marketing indirectly influences customer breadth, (8) service quality indirectly has an influence on customer satisfaction through purchasing decisions and (9) prices indirectly have a major influence on customer satisfaction through purchasing decisions.